Optically Transparent and Low‐CTE Polyethersulfone‐Based Nanocomposite Films for Flexible Display. Issue 24 (9th November 2020) - Kim, Jae‐Hyun; Lan, Nguyen Xuan Viet; Kulkarni, Uddhav; Kim, Chanho; Cho, Sung Min; Yoo, Pil J.; Kim, Dukjoon; Schroeder, Marc; Yi, Gi‐Ra
Abstract: Optically transparent and thermo‐mechanically stable nanocomposite films of polyethersulfone (PESU) and core–shell nanoparticles are prepared by a solvent casting and heat pressing method. As a filler, reactive ZnS‐SiO2 core–shell nanoparticles are prepared by a modified sol–gel process, of which reactive aromatic amine groups are chemically bonded with the polymer matrix. For optical transparency, the shell thickness is adjusted and the core diameter of the core–shell nanoparticles is adjusted to match the refractive index of PESU ( n PESU  = 1.65). For the composite film with more than 15 wt% of core–shell nanoparticles in PESU, the coefficient of thermal expansion is significantly reduced down to 12 ppm °C −1 in the temperature range of 30–90 °C, which is 80% less than the value of the bare PESU film (≈65 ppm °C −1 ). Furthermore, their mechanical property is also significantly improved. For 15 and 30 wt%, PESU nanocomposite films show 64 and 74 MPa of yield strength and 1.36 and 2.0 GPa of Young's modulus, respectively, while pure PESU films show only 44 MPa of the yield strength and 0.64 GPa of Young's modulus. Finally, the organic light emitting diode device is demonstrated on the PESU nanocomposite substrate. Abstract : Polymer composite films are fabricated as a flexible OLED display substrate. ZnS@SiO2 core‐shell nanoparticles are utilized as fillers in polyethersulfone (PESU), which show lower coefficient of thermal expansion (CTE) than 20 ppm °C −1 and high relative transmittance (>94%) by matching refractive‐index between filler and matrix. In addition, OLED display is demonstrated on a nanocomposite substrate.